Age-related changes in the glutathione redox system - Erden-İnal, Mine; Sunal, Emine; Kanbak, Güngör (Cell biochemistry and function, 2002)
The effect of aging on the glutathione redox system was evaluated in this study. For this purpose, we determined reduced glutathione (GSH) and oxidized glutathione (GSSG) in whole blood, glutathione peroxidase (GPx) and glutathione reductase (GSSGR) in erythrocytes and selenium (Se) in plasma in 176 healthy individuals. We also calculated GSH/GSSG molar ratios. These subjects were divided into five groups: group 1 (n = 25; 0.2–1 years old); group 2 (n = 28; 2–11 years old); group 3 (n = 23; 12–24 years old); group 4 (n = 40; 25–40 years old); group 5 (n = 60; 41–69 years old). GSH levels in groups 1 and 5 were significantly lower than the other groups (p< 0.001). Conversely, GSSG levels were significantly high in these periods (p< 0.001). The GSH/GSSG molar ratio was found to be low both in the first year of life and in the oldest group (p< 0.001, respectively). GPx activity in group 5 was increased as compared to the other groups (p< 0.001). GSSGR activity was significantly lower in the oldest groups than in the other groups (p< 0.001). Se levels were found to be low in the oldest group (p< 0.001). Selenium levels of women in group 5 were significantly high as compared to the men (p< 0.01). We found negative correlations between age and GSH levels (r = 0.402; p< 0.001), selenium levels (r = 0.454; p< 0.001), GSH/GSSG molar ratio (r = 0.557; p< 0.001) and GSSGR activity (r = 0.556; p< 0.001). There were positive correlations between age and GPx (r = 0.538; p< 0.001) and GSSG level (r = 0.551; p< 0.001). In conclusion, our findings show that the glutathione redox system is affected by age. Oxidative stress increases during the aging process. There is no effect of aging on the glutathione redox system according to sex except for the Se level. Copyright © 2001 John Wiley & Sons, Ltd.